Attitudes of the Elderly towards Social Service Provided in Nursery Home in Baghdad City (Journal Of Educational and Psychological Researches, 2022)
AbstractThrough social service tasks for the elderly, it natural for elder people to have some attitudes about the quality and nature of provided services, whether negative or positive. Accordingly, the current research is an attempt to investigate the attitudes of the elderly toward the social service provided to them in the nursery homes. The research sample included 60 elderly people chosen from the nursey home at Al-Karrada district and then a scale of attitudes was administered to them that had proved its reliability and validity. The study concluded with a set of recommendations and suggestions were.